Depressão,vinculação e relações amorosas de pessoas em luto - Feio, Joana Filipa Duarte (2014)
This research sought to understand the relationship between depression and attachment in romantic relationships of people mourning the death of a spouse. 107 individuals participated in this study were widowed between 45 and 96 years old, 23 of them males and 84 females. To evaluate the variables the instruments used were: the Adult Attachment Scale-VAS in order to evaluate the binding in adults, The Beck Depression Inventory-BDI to assess depressive symptoms, and a questionnaire Love relations constructed to understand the relationship with the deceased spouse. The results obtained in this investigation as to the time of widowhood, and duration of depression relationship, bonding and loving relationship were inconclusive. However the results showed that the pattern of binding relates negatively with anxious depression, and depression increases with age. Still can conclude that there is a relationship between depression, and quality of attachment as well as between them and the relationship.